2019
DOI: 10.1038/s41598-018-37206-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multiple adsorption mechanisms for efficient removal of ofloxacin from water using lignin-based adsorbents

Abstract: Two series of lignin (LN)-based adsorbents, namely, cross-linked lignin (LNEs) with different crosslinking densities and carboxymethyl cross-linked lignin (LNECs) with various degrees of carboxymethyl substitution, were prepared to remove ofloxacin (OFL), a popular fluoroquinolone (FQ) antibiotic, from water. LNEs and LNECs exhibited satisfactory performance in OFL adsorption. Both of them had high adsorption capacity (the maximum contribution of 0.828 mmol/g), good anti-interference to some inorganic salts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…A similar assumption was also considered in a previous report on analyzing the adsorption behavior of lignin-based polymers. [29] The dipole moment is an important physical property of a molecule that is vital in determining molecular polarity and is a key factor for understanding and quantifying the intermolecular interactions. [30,31] Dipole moments occur when there is a charge separation between two ions in an ionic bond or between atoms in a covalent bond due to the differences in their electronegativity, which tends to orient a molecule in a polarized dielectric.…”
Section: Structure Of Lignin Polymermentioning
confidence: 99%
“…A similar assumption was also considered in a previous report on analyzing the adsorption behavior of lignin-based polymers. [29] The dipole moment is an important physical property of a molecule that is vital in determining molecular polarity and is a key factor for understanding and quantifying the intermolecular interactions. [30,31] Dipole moments occur when there is a charge separation between two ions in an ionic bond or between atoms in a covalent bond due to the differences in their electronegativity, which tends to orient a molecule in a polarized dielectric.…”
Section: Structure Of Lignin Polymermentioning
confidence: 99%
“…Here, the OFL had a good hydrophilicity (i.e. log K ow = − 0.39) and the highest sorption values did not all appear at the lowest solubility, which suggested that the sorption of OFL by U.P- biochars was not entirely dependent on the hydrophobic interaction 38 , 39 .…”
Section: Resultsmentioning
confidence: 94%
“…Thus, the sorption capacity might reduce through the weakening ionic exchange and cationic–π interactions between biochar and OFL. However, the sorption capacity of U.P- biochars also exhibited a relatively high level at neutrality, which was probably due to H-bond, π–π and hydrophobic interactions being involved in the sorption process 38 . Meanwhile, the positive surface charge of U.P- biochars decreased due to the deprotonation effect, leading to significant reduction in the electrostatic repulsion between U.P- biochars and OFL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations